Mask blank and method of manufacturing the same, phase shift mask and method of manufacturing the same

By introducing a film layer of specific materials and structures into the phase shift mask blank, the problems of insufficient high resolution and etch resistance of phase shift masks in the prior art are solved, and the manufacturing of phase shift masks with high resolution, small linewidth and good uniformity is realized.

CN119805847BActive Publication Date: 2026-11-06QINGFANG TECHNOLOGY (JINAN) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510095453.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2026-11-06
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Existing phase-shifting masks cannot simultaneously satisfy high resolution and excellent etch resistance, while the substrate is prone to over-etching.

Method used

A phase-shifting mask with optimized light field distribution and reduced resist film loss is prepared by depositing each film layer using a mask blank with specific materials and structures, including a transparent substrate, an etching stop film, a phase-shifting film, a light-shielding film, and a hard mask, through magnetron sputtering.

Benefits of technology

This achieves high-resolution, low-linewidth phase-shift masks, reduces resist film thickness loss, avoids excessive etching of the substrate, and improves the uniformity and resolution of pattern transfer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119805847B_ABST
    Figure CN119805847B_ABST
Patent Text Reader

Abstract

This invention provides a mask blank and its manufacturing method, a phase-shifting mask and its manufacturing method; the mask blank includes a transparent substrate, an etching stop film, a phase-shifting film, a light-shielding film and a hard mask stacked sequentially, wherein the etching stop film is made of a metallic element and a non-metallic element, the metallic element being selected from one of Cr, Ta, Hf, Zr, Al, W and Ni; the phase-shifting film is made of a molybdenum silicon compound and a non-metallic element; the light-shielding film is made of Cr and a non-metallic element; the hard mask is made of silicon or a molybdenum silicon compound and a non-metallic element; the non-metallic element is selected from one or more of C, O, N, B and P.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor manufacturing technology, and more specifically, to a mask blank and its manufacturing method, and a phase-shifting mask and its manufacturing method. Background Technology

[0002] In the manufacturing process of semiconductor devices, photolithography is commonly used to form fine patterns. During the pattern miniaturization process using photolithography, in addition to miniaturizing the mask pattern of the transfer mask, it is also necessary to minimize the wavelength of the exposure light source. In recent years, deep ultraviolet (DUV) lithography has advanced to using ArF excimer lasers, with a wavelength of 193 nm.

[0003] Masks mainly include binary masks and phase-shifting masks. Phase-shifting masks are manufactured by forming a mask pattern on a mask blank through corresponding photolithography processes. The mask blank is composed of different functional film layers, such as a phase-shifting film, a light-blocking film, and a photoresist film. In a phase-shifting mask, the phase of light passing through the semi-transparent region is shifted, resulting in a phase difference of approximately 180° between the semi-transparent and transparent regions. This causes the light at the boundary between the semi-transparent and transparent regions to cancel each other out, partially reducing the diffraction spread effect, altering the spatial light intensity distribution, and thus improving the spatial pattern contrast at the boundary.

[0004] To obtain fine photomask patterns, on the one hand, the resist pattern needs to be finer, thus requiring a thinner resist film. If the resist film thickness is not reduced, excessive thickness will increase the aspect ratio of the resist portion used as the light-shielding layer, i.e., the ratio of resist film thickness to pattern width will increase, leading to easy deterioration of the pattern shape and reduced resolution of the transferred pattern on the light-shielding layer using it as an etching mask. In extreme cases, part of the resist pattern may collapse or peel off, resulting in pattern blanks. On the other hand, when using a resist film as an etching mask for light-shielding film patterning, common light-shielding films (such as those containing chromium compounds) are usually patterned by dry etching, and most etching conditions also have a significant etching effect on organic films such as resist films. If a thin resist film is used as a mask to etch the light-shielding film, the thin resist film is not enough to block the long-term attack of plasma, which will cause the resist film to be damaged during the etching process, and thus cause the shape of the resist pattern to change, making it difficult to accurately transfer the original resist pattern onto the light-shielding film.

[0005] Based on existing patterning processes, achieving high resolution requires thinning the resist film; however, ensuring good etch resistance during patterning necessitates increasing its thickness. Consequently, existing organic resist films struggle to simultaneously satisfy both high resolution and excellent etch resistance.

[0006] Furthermore, when using a mask blank composed of a resist film, a light-shielding film, a phase-shifting film, and a light-transmitting substrate as a mask, the light-shielding layer is used as a mask during the dry etching process of the phase-shifting film. In this process, the light-transmitting substrate is easily over-etched, and there is uneven etching, which leads to uneven phase shift during the subsequent pattern transfer process.

[0007] Therefore, in order to form higher resolution photomask patterns, achieve thin-film resist film, improve etching resistance, and reduce excessive etching of the substrate, it is urgent to provide a phase-shifting mask and its manufacturing method. Summary of the Invention

[0008] The main objective of this invention is to provide a mask blank and its manufacturing method, and a phase-shifting mask and its manufacturing method, so as to solve the problem that existing phase-shifting masks in the prior art cannot simultaneously meet the requirements of high resolution and excellent etch resistance, and also have the problem that the substrate is prone to over-etching.

[0009] To achieve the above objectives, the present invention provides a mask blank comprising a transparent substrate, an etching stop film, a phase shift film, a light-shielding film, and a hard mask stacked sequentially. The etching stop film is made of a metallic element and a non-metallic element, wherein the metallic element is selected from one of Cr, Ta, Hf, Zr, Al, W, and Ni; the phase shift film is made of a molybdenum-silicon compound and a non-metallic element; the light-shielding film is made of Cr and a non-metallic element; the hard mask is made of silicon or a molybdenum-silicon compound and a non-metallic element; the non-metallic element is selected from one or more of C, O, N, B, and P; the light density of the light-shielding film under an exposure light source with a wavelength ≤250 nm is 1.5–2.1; the optical density of the stacked structure obtained by sequentially stacking the etching stop film, the phase shift film, and the light-shielding film under an exposure light source with a wavelength ≤250 nm is 2.9–3.3; the transmittance of the etching stop film and the phase shift film under an exposure light source with a wavelength of 193 nm is 3–35%, and the phase difference is 175–182°.

[0010] Furthermore, the etching stop film has a single-layer or multi-layer structure with a thickness of 1–10 nm. In each layer of the etching stop film, the atomic percentage of Cr is ≥30 at.%, the atomic percentage of C is ≤15 at.%, and the balance is other elements.

[0011] Furthermore, the phase-shifting film has a single-layer or multi-layer structure with a thickness of 60–90 nm.

[0012] Furthermore, the phase-shifting film has a monolayer structure, wherein the atomic percentage of Mo is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤20 at.%, and the atomic percentage of N is ≥40 at.%.

[0013] Furthermore, the phase-shifting film has a two-layer structure. The atomic percentage of O in the layer away from the etching stop film is lower than that in the layer near the etching stop film. Specifically, in the layer near the etching stop film, the atomic percentage of Mo is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤25 at.%, and the atomic percentage of N is ≥35 at.%; in the layer away from the transparent substrate, the atomic percentage of Mo is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤20 at.%, and the atomic percentage of N is ≥40 at.%. The thickness of the layer near the etching stop film is 5–45 nm, and the thickness of the layer away from the etching stop film is 30–70 nm.

[0014] Furthermore, the light-shielding film has a single-layer or multi-layer structure with a thickness of 30–65 nm.

[0015] Furthermore, the light-shielding film has a single-layer structure, wherein the atomic percentage of Cr is ≥30 at.%, the sum of the atomic percentages of O and N is ≤55 at.%, and the atomic percentage of C is ≤15 at.%.

[0016] Furthermore, the light-shielding film has a two-layer structure. The relative refractive index of the film layer on the side away from the phase-shifting film is greater than that of the film layer on the side closer to the phase-shifting film. Specifically, in the film layer on the side closer to the phase-shifting film, the atomic percentage of Cr is ≤43 at.%, the sum of the atomic percentages of O and N is ≥37 at.%, and the atomic percentage of C is ≤20 at.%. In the layer on the side away from the phase-shifting film, the atomic percentage of Cr is ≥35 at.%, and the sum of the atomic percentages of O and N is ≤65 at.%. The thickness of the film layer on the side closer to the phase-shifting film is 35–55 nm, and the thickness of the layer on the side away from the phase-shifting film is 2–10 nm.

[0017] Furthermore, the light-shielding film also includes a diffusion barrier layer disposed on the side close to the phase-shifting film, wherein the atomic percentage of Cr in the diffusion barrier layer is ≥35 at.%, and the sum of the atomic percentages of O and N is ≤65 at.%; the thickness of the diffusion barrier layer is 2 to 10 nm.

[0018] Furthermore, the light-shielding film has a three-layer structure, comprising a first light-shielding layer, a second light-shielding layer, and a third light-shielding layer stacked in sequence. The first light-shielding layer is disposed on the side close to the phase-shifting film, and the third light-shielding layer is disposed away from the phase-shifting film. In the first light-shielding layer, the atomic percentage of Cr is ≤45 at.%, the sum of the atomic percentages of O and N is ≥35 at.%, and the atomic percentage of C is ≤20 at.%. In the second light-shielding layer, the atomic percentage of Cr is ≥45 at.%, and the atomic percentage of non-metallic elements is ≤55 at.%. In the third light-shielding layer, the atomic percentage of Cr is ≤45 at.%, the sum of the atomic percentages of O and N is ≥35 at.%, and the atomic percentage of C is ≤20 at.%. The thickness of the first light-shielding layer is 10–35 nm, the thickness of the second light-shielding layer is 2–10 nm, and the thickness of the third light-shielding layer is 10–30 nm.

[0019] Furthermore, the light-shielding film has a four-layer structure, comprising a first light-shielding layer, a second light-shielding layer, a third light-shielding layer, and a fourth light-shielding layer stacked together. The first light-shielding layer is disposed on the side closest to the phase-shifting film, and the fourth light-shielding layer is disposed on the side furthest from the phase-shifting film. Specifically, in the first light-shielding layer, the atomic percentage of Cr is ≤45 at.%, the sum of the atomic percentages of O and N is ≥40 at.%, and the atomic percentage of C is ≤15 at.%. In the second light-shielding layer, the atomic percentage of Cr is ≥35 at.%, and the atomic percentage of the third light-shielding layer is ≥35 at.%. The atomic percentage of Cr in the third light-shielding layer is ≤65 at.%, the atomic percentage of O and N in the third light-shielding layer is ≤45 at.%, the atomic percentage of C in the third light-shielding layer is ≥40 at.%, the atomic percentage of C in the fourth light-shielding layer is ≥35 at.%, and the atomic percentage of O and N in the fourth light-shielding layer is ≤65 at.%. The thickness of the first light-shielding layer is 15–30 nm, the thickness of the second light-shielding layer is 2–10 nm, the thickness of the third light-shielding layer is 15–30 nm, and the thickness of the fourth light-shielding layer is 2–10 nm.

[0020] Furthermore, the hard mask has a single-layer or multi-layer structure with a thickness of 2–15 nm. In each layer of the hard mask, the atomic percentage of Si is ≥30 at.%, and the sum of the atomic percentages of O and N is ≤70 at.%.

[0021] Furthermore, the mask blank also includes a resist film, which is disposed on the surface of the hard mask away from the light-transmitting substrate; the thickness of the resist film is 60–200 nm.

[0022] To achieve the above objectives, another aspect of the present invention provides a method for manufacturing a mask blank, wherein an etching stop film, a phase shift film, a light-shielding film and a hard mask are sequentially deposited on one side surface of a light-transmitting substrate, wherein the etching stop film, the phase shift film, the light-shielding film and the hard mask have the same definitions as those described above.

[0023] Furthermore, magnetron sputtering is used for deposition; during the deposition of the etching stop film, phase shift film, light-shielding film and hard mask, the working pressure is independently 0.1 to 0.4 Pa, the sputtering power is independently 200 to 3500 W, and the working gas is independently one or more of Ar, He, O2, N2, N2O, NO, NO2, CO2, CO and CH4.

[0024] Another aspect of the present invention provides a method for manufacturing a phase-shifting mask, using the mask blank provided in this application as raw material to manufacture the phase-shifting mask, the method comprising:

[0025] Step S1: A first resist is coated on the side of the hard mask away from the light-transmitting substrate in the mask blank to form a resist film. Exposure, baking and development are performed in sequence to obtain a first stacked structure containing a patterned first resist film.

[0026] Step S2: Using the patterned first resist film in the first stacked structure as a mask, the hard mask in the first stacked structure is etched, and after cleaning to remove the patterned first resist film, a second stacked structure containing the patterned hard mask is obtained.

[0027] Step S3: Using the patterned hard mask in the second stacked structure as a mask, the light-shielding film in the second stacked structure is etched to obtain a third stacked structure containing a patterned first light-shielding film.

[0028] Step S4: Using the patterned first light-shielding film in the third stacked structure as a mask, the phase shift film in the third stacked structure is etched. During the etching process in step S4, the patterned hard mask is removed, and a fourth stacked structure containing the patterned phase shift film is obtained.

[0029] Step S5: Coat the surface of the fourth stacked structure away from the light-transmitting substrate with a second photoresist, and then expose, bake and develop in sequence to obtain a fifth stacked structure containing a patterned second photoresist film.

[0030] In step S6, the patterned second resist film in the fifth stacked structure is used as a mask to etch the first light-shielding film in the fifth stacked structure. During the etching process in step S6, the etching stop film is etched away. After cleaning and removing the patterned second resist film, a phase shift mask containing the patterned second light-shielding film is obtained.

[0031] Furthermore, the hard mask is a single-layer structure, or a two-layer structure, where the etching rate of the layer closer to the light-shielding film is lower than the etching rate of the layer farther from the light-shielding film; or, the hard mask is a three-layer structure, where the etching rate of the middle layer is lower than the etching rate of the other two layers.

[0032] Another aspect of the present invention provides a phase shift mask, which is manufactured using the manufacturing method of the phase shift mask described above provided in this application.

[0033] Using the technical solution of this invention, a hard mask is provided on the surface of the mask blank on the side away from the light-transmitting substrate. Since the hard mask is thinner, the etching process during the manufacturing of the phase-shifting mask reduces the loss of the resist film on its side surface, thereby reducing the thickness of the resist film and achieving high resolution and small linewidth.

[0034] Furthermore, since the etching time required for hard mask patterning is shorter than that required for light-shielding film patterning, the hard mask setup can mitigate the load effect that occurs during pattern formation and improve the linearity of CD (critical dimension).

[0035] Compared to mask blanks without an etching stop film, the mask blank provided in this application has an etching stop film on the surface of the light-transmitting substrate. During the etching process of the phase-shifting film using the light-blocking film as a mask, excessive etching of the light-transmitting substrate can be avoided, thus solving the problem of uneven phase shift during the subsequent pattern transfer process. Attached Figure Description

[0036] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0037] Figure 1 A schematic diagram of the cross-sectional structure of the mask blank provided in this application is shown;

[0038] Figure 2 A schematic cross-sectional view of a mask blank in one embodiment of this application is shown.

[0039] Figure 3 A cross-sectional schematic diagram of the first stacked structure is shown;

[0040] Figure 4 A cross-sectional schematic diagram of the second stacked structure is shown;

[0041] Figure 5 A cross-sectional schematic diagram of the third stacked structure is shown;

[0042] Figure 6 A cross-sectional schematic diagram of the fourth stacked structure is shown;

[0043] Figure 7 A cross-sectional schematic diagram of the fifth stacked structure is shown;

[0044] Figure 8 A schematic diagram of the cross-sectional structure of the phase-shifting mask is shown;

[0045] Figure 9 A schematic cross-sectional view of the mask blank for Comparative Example 2 is shown.

[0046] The above figures include the following reference numerals:

[0047] 10. Transparent substrate; 20. Etching stop film; 30. Phase shift film; 31. Patterned phase shift film; 40. Light-shielding film; 41. Patterned first light-shielding film; 42. Patterned second light-shielding film; 50. Hard mask; 51. Patterned hard mask; 60. Resist film; 61. Patterned first resist film; 62. Patterned second resist film. Detailed Implementation

[0048] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the embodiments.

[0049] As described in the background section, existing phase-shifting masks suffer from difficulties in simultaneously achieving high resolution and excellent etch resistance, and also exhibit the problem of over-etching of the substrate. To address these technical problems, the first aspect of this application provides a mask blank. Figure 1 A cross-sectional structural diagram of the mask blank is shown. The mask blank includes a light-transmitting substrate 10, an etching stop film 20, a phase shift film 30, a light-shielding film 40, and a hard mask 50, which are stacked in sequence.

[0050] The etching stop film 20 is made of metallic and non-metallic elements, with the metallic elements selected from one of Cr, Ta, Hf, Zr, Al, W, and Ni; the phase shift film 30 is made of molybdenum-silicon compound and non-metallic elements; the light-shielding film 40 is made of Cr and non-metallic elements; the hard mask 50 is made of silicon or molybdenum-silicon compound and non-metallic elements, with the non-metallic elements selected from one or more of C, O, N, B, and P; the light density of the light-shielding film 40 under an exposure light source with a wavelength ≤250nm is 1.5–2.1; the stacked structure obtained by sequentially stacking the etching stop film 20, phase shift film 30, and light-shielding film 40 has an optical density of 2.9–3.3 under an exposure light source with a wavelength ≤250nm; the transmittance of the etching stop film 20 and the phase shift film 30 under an exposure light source with a wavelength of 193nm is 3–35%, and the phase difference is 175–182°.

[0051] In the process of manufacturing a phase-shifting mask, the hard mask 50 reduces the loss of the resist film 60 on its surface, allowing for a thinner resist film 60 and achieving high resolution and low linewidth. Compared to other types, the hard mask 50 made of the above-mentioned materials is advantageous in reducing the thickness of the resist film 60 and minimizing its loss during the patterning process.

[0052] The mask blank provided in this application is provided with an etching stop film 20. Compared with a mask blank without an etching stop film 20, during the etching of the phase shift film 30, over-etching of the light-transmitting substrate 10 can be avoided, thus improving the uniformity of optical performance during the subsequent pattern transfer process. Compared with other types, the etching stop film 20 using the aforementioned specific material, and the material of the etching stop film 20 being different from that of the phase shift film 30 and the light-transmitting substrate 10, is beneficial in preventing over-etching of the light-transmitting substrate 10 and improving the uniformity of optical performance during the subsequent pattern transfer process.

[0053] Compared to other types, the phase-shifting film 30 made of the aforementioned specific material can optimize the light field distribution, enable destructive interference, reduce the brightness of dark areas in the light field, and increase the brightness of bright areas, thereby improving the resolution of the fabricated phase-shifting mask and reducing the linewidth. Furthermore, compared to other ranges, limiting the optical density of the etching stop film 20, the phase-shifting film 30, and the light-shielding film 40 to the aforementioned specific range allows the mask blank to effectively block the exposure light source, improving the resolution of the phase-shifting mask and consequently increasing the resolution of the pattern formed on the wafer surface.

[0054] In a preferred embodiment, the etching stop film 20 has a single-layer or multi-layer structure with a thickness of 1 to 10 nm. In each layer of the etching stop film 20, the atomic percentage of Cr is ≥30 at.%, the atomic percentage of C is ≤15 at.%, and the balance is other elements.

[0055] In a preferred embodiment, the phase-shifting film 30 has a single-layer or multi-layer structure with a thickness of 60–90 nm.

[0056] In a preferred embodiment, the phase-shifting film 30 has a single-layer structure, wherein the atomic percentage of Mo is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤20 at.%, and the atomic percentage of N is ≥40 at.%.

[0057] In a preferred embodiment, the phase-shifting film 30 has a two-layer structure. The atomic percentage of O in the layer on the side away from the etching stop film 20 is lower than that in the layer on the side closer to the etching stop film 20. Specifically, in the layer on the side closer to the etching stop film 20, the atomic percentage of Mo is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤25 at.%, and the atomic percentage of N is ≥35 at.%; in the layer on the side away from the etching stop film 20, the atomic percentage of Mo is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤20 at.%, and the atomic percentage of N is ≥40 at.%. The thickness of the layer on the side closer to the etching stop film 20 is 5–45 nm, and the thickness of the layer on the side away from the etching stop film 20 is 30–70 nm.

[0058] In a preferred embodiment, the light-shielding film 40 has a single-layer or multi-layer structure with a thickness of 30–65 nm.

[0059] In a preferred embodiment, the light-shielding film 40 has a single-layer structure, and the atomic percentage of Cr in the light-shielding film 40 is ≥30 at.%, the sum of the atomic percentages of O and N is ≤55 at.%, and the atomic percentage of C is ≤15 at.%.

[0060] In a preferred embodiment, the light-shielding film 40 has a two-layer structure, with the relative refractive index of the film layer on the side away from the phase-shifting film 30 being greater than that on the side closer to the phase-shifting film 30; wherein, in the film layer on the side closer to the phase-shifting film 30, the atomic percentage of Cr is ≤43 at.%, the sum of the atomic percentages of O and N is ≥37 at.%, and the atomic percentage of C is ≤20 at.%; in the film layer on the side away from the phase-shifting film 30, the atomic percentage of Cr is ≥35 at.%, and the sum of the atomic percentages of O and N is ≤65 at.%; the thickness of the film layer on the side closer to the phase-shifting film 30 is 35–55 nm, and the thickness of the film layer on the side away from the phase-shifting film 30 is 2–10 nm.

[0061] In a more preferred embodiment, the light-shielding film 40 with the two-layer structure further includes a diffusion-blocking layer disposed on the side close to the phase-shifting film 30, wherein the atomic percentage of Cr in the diffusion-blocking layer is ≥35 at.%, and the sum of the atomic percentages of O and N is ≤65 at.%; the thickness of the diffusion-blocking layer is 2 to 10 nm.

[0062] In a preferred embodiment, the light-shielding film 40 has a three-layer structure, comprising a first light-shielding layer, a second light-shielding layer, and a third light-shielding layer stacked together. The first light-shielding layer is disposed on the side close to the phase-shifting film 30, and the third light-shielding layer is disposed on the side away from the phase-shifting film 30. In the first light-shielding layer, the atomic percentage of Cr is ≤45 at.%, the sum of the atomic percentages of O and N is ≥35 at.%, and the atomic percentage of C is ≤20 at.%. In the second light-shielding layer, the atomic percentage of Cr is ≥45 at.%, and the atomic percentage of non-metallic elements is ≤55 at.%. In the third light-shielding layer, the atomic percentage of Cr is ≤45 at.%, the sum of the atomic percentages of O and N is ≥35 at.%, and the atomic percentage of C is ≤20 at.%. The thickness of the first light-shielding layer is 10–35 nm, the thickness of the second light-shielding layer is 2–10 nm, and the thickness of the third light-shielding layer is 10–30 nm.

[0063] In a preferred embodiment, the light-shielding film 40 has a four-layer structure, comprising a first light-shielding layer, a second light-shielding layer, a third light-shielding layer, and a fourth light-shielding layer stacked in sequence. The first light-shielding layer is disposed on the side close to the phase-shifting film 30, and the fourth light-shielding layer is disposed on the side away from the phase-shifting film 30. In the first light-shielding layer, the atomic percentage of Cr is ≤45 at.%, the sum of the atomic percentages of O and N is ≥40 at.%, and the atomic percentage of C is ≤15 at.%. In the second light-shielding layer, the atomic percentage of Cr is ≥35 at.%, and the atomic percentage of non-metallic elements is ≥35 at.%. The atomic percentage of the first light-shielding layer is ≤65 at.%; the atomic percentage of Cr in the third light-shielding layer is ≤45 at.%, the sum of the atomic percentages of O and N is ≥40 at.%, and the atomic percentage of C is ≤15 at.%; the atomic percentage of Cr in the fourth light-shielding layer is ≥35 at.%, and the sum of the atomic percentages of O and N is ≤65 at.%; the thickness of the first light-shielding layer is 15–30 nm, the thickness of the second light-shielding layer is 2–10 nm, the thickness of the third light-shielding layer is 15–30 nm, and the thickness of the fourth light-shielding layer is 2–10 nm.

[0064] In a preferred embodiment, the hard mask 50 is a single-layer or multi-layer structure with a thickness of 2–15 nm. Compared to other ranges, limiting the thickness of the hard mask 50 to the above range is beneficial because the thickness of the hard mask 50 is relatively thin. During the fabrication of the phase-shifting mask, etching it helps to reduce the loss of the resist film 60 on its surface, which in turn helps to reduce the thickness of the resist film 60, thereby achieving higher resolution and smaller linewidth.

[0065] In a preferred embodiment, the atomic percentage of Si in each layer of the hard mask 50 is ≥30 at.%, and the sum of the atomic percentages of O and N is ≤70 at.%.

[0066] In a preferred embodiment, such as Figure 2 As shown, the mask blank also includes a resist film 60, which is disposed on the surface of the hard mask 50 away from the transparent substrate 10. The resist film 60 facilitates exposure processing, patterning, and subsequent fabrication of phase-shift masks.

[0067] In order to improve the resolution of the pattern formed by etching, in a preferred embodiment, the thickness of the resist film 60 is 60-200 nm.

[0068] In order to improve the resolution of the pattern formed by etching, in a preferred embodiment, the resist film 60 is a chemically amplified resist.

[0069] It should be noted that the thickness of each of the above-mentioned films in this application can be measured by XRR (X-ray reflectance); the chemical composition of the films can be measured by XPS (X-ray photoelectron spectroscopy).

[0070] The second aspect of this application also provides a method for manufacturing a mask blank, the method comprising sequentially depositing an etching stop film 20, a phase shift film 30, a light-shielding film 40 and a hard mask 50 on one side surface of a light-transmitting substrate 10, wherein the etching stop film 20, the phase shift film 30, the light-shielding film 40 and the hard mask 50 have the same definition as those described above in this application.

[0071] An etching stop film 20, a phase shift film 30, a light-shielding film 40, and a hard mask 50 are sequentially prepared on one side surface of a light-transmitting substrate 10 using a deposition method, thereby obtaining the mask blank of the above-mentioned stacked structure of this application.

[0072] In a preferred embodiment, magnetron sputtering is used for deposition. Compared to other methods, magnetron sputtering allows for better control of the deposition effect, thereby improving the performance of each film layer and ultimately increasing the resolution of the phase-shift mask.

[0073] In a preferred embodiment, during the deposition of the etching stop film 20, the phase shift film 30, the light-shielding film 40, and the hard mask 50, the working pressure is independently 0.1 to 0.4 Pa, the sputtering power is independently 200 to 3500 W, and the working gas is independently one or more of Ar, He, O2, N2, N2O, NO, NO2, CO2, CO, and CH4.

[0074] A third aspect of this application also provides a method for manufacturing a phase-shifting mask, using the mask blank provided in this application as raw material to manufacture the phase-shifting mask. The manufacturing method includes:

[0075] Step S1: A first resist is coated on the side of the hard mask 50 away from the light-transmitting substrate 10 in the mask blank to form a resist film 60. Exposure, baking, and development are then performed sequentially to obtain a first stacked structure containing a patterned first resist film 61 (e.g., ...). Figure 3 (as shown);

[0076] Step S2: Using the patterned first resist film 61 in the first stacked structure as a mask, the hard mask 50 in the first stacked structure is etched. After cleaning to remove the patterned first resist film 61, a second stacked structure containing the patterned hard mask 51 is obtained (e.g., ...). Figure 4 (as shown);

[0077] Step S3: Using the patterned hard mask 51 in the second stacked structure as a mask, the light-shielding film 40 in the second stacked structure is etched to obtain a third stacked structure containing the patterned first light-shielding film 41 (e.g., ...). Figure 5 (as shown);

[0078] In step S4, using the patterned first light-shielding film 41 in the third stacked structure as a mask, the phase-shifting film 30 in the third stacked structure is etched. During the etching process in step S4, the patterned hard mask 51 is removed, resulting in a fourth stacked structure containing the patterned phase-shifting film 31 (e.g., ...). Figure 6 (as shown);

[0079] Step S5: A second resist is coated on the surface of the fourth stacked structure away from the light-transmitting substrate 10, and exposure, baking, and development are performed sequentially to obtain a fifth stacked structure containing a patterned second resist film 62 (e.g., ...). Figure 7 (as shown);

[0080] Step S6: Using the patterned second resist film 62 in the fifth stacked structure as a mask, the first light-shielding film 41 in the fifth stacked structure is etched. During the etching process in step S6, the etching stop film 20 is etched away. After cleaning to remove the patterned second resist film 62, a phase-shifting mask containing the patterned second light-shielding film 42 is obtained (e.g., ...). Figure 8 (As shown).

[0081] In a preferred embodiment, the etching is preferably dry etching.

[0082] In a preferred embodiment, in step S2, a mixture of SF6 and He with a gas flow rate ratio of 1:15 is used to dry etch the hard mask 50 in the first stacked structure; in step S3, a mixture of Cl2 and O2 with a gas flow rate ratio of 10:1 is used to dry etch the light-shielding film 40 in the second stacked structure; in step S4, a mixture of SF6 and He with a gas flow rate ratio of 1:15 is used to dry etch the phase-shifting film 30 in the third stacked structure; and in step S6, a mixture of Cl2 and O2 with a gas flow rate ratio of 7:2 is used to dry etch the first light-shielding film 41 in the fifth stacked structure.

[0083] Using the mask blanks with the specific stacked structure and material provided in this application as raw materials and manufacturing them using the above-described manufacturing method, a phase-shifting mask with high resolution and excellent etch resistance can be obtained.

[0084] In a preferred embodiment, the hard mask 50 is a single-layer structure, or the hard mask 50 is a two-layer structure, where the etching rate of the film layer closer to the light-shielding film 40 is lower than the etching rate of the film layer farther from the light-shielding film 40; or the hard mask 50 is a three-layer structure, where the etching rate of the middle layer is lower than the etching rate of the other two adjacent layers.

[0085] A fourth aspect of this application also provides a phase-shifting mask, which is manufactured using the manufacturing method described above. By using the mask blank with the specific stacked structure and material described above as provided in this application as raw material and manufacturing it using the above manufacturing method, a phase-shifting mask with high resolution and excellent etch resistance can be obtained.

[0086] The present application will be further described in detail below with reference to specific embodiments, which should not be construed as limiting the scope of protection claimed in the present application.

[0087] Example 1

[0088] A method for manufacturing a mask blank, comprising:

[0089] (1) Prepare a transparent substrate 10 with a size of 152mm×152mm×6.35mm as a mask blank, and clean it. The root mean square roughness Rq of the surface of the transparent substrate 10 is less than 0.5nm.

[0090] (2) Preparation of etching stop film 20:

[0091] DC reactive magnetron sputtering was performed on one side surface of the transparent substrate 10. The target material was a chromium (Cr) target, and a mixture of Ar, N2 and O2 was used as the working gas (where the gas flow ratio of Ar, O2 and N2 was 60:1:20). The working gas pressure was set to 0.13 Pa, and the power of the DC power supply was 600 W, resulting in a CrON monolayer film with a thickness of 3 nm.

[0092] The chemical composition of the CrON monolayer film was determined by XPS (X-ray photoelectron spectroscopy). The atomic percentages of each element in the CrON monolayer film were as follows: 55 at.% for Cr, 8 at.% for O, and 37 at.% for N.

[0093] (3) Preparation of phase-shifting film 30:

[0094] DC magnetron sputtering was performed on the side of the etching stop film 20 away from the transparent substrate 10. The target material was a molybdenum silicon (MoSi) alloy target. A mixture of Ar and N2 gas was used as the working gas (where N2 gas flow rate / (Ar gas flow rate + N2 gas flow rate) = 85%). The working gas pressure was set to 0.13 Pa, and the power of the DC power supply was 600 W. A MoSi monolayer film (i.e., phase shift film 30) with a thickness of 66 nm was obtained.

[0095] The chemical composition of the MoSi monolayer film was determined by XPS (X-ray photoelectron spectroscopy), and the contents of each element in the MoSi monolayer film were found to be: Mo = 4.4 at.%, Si = 40.1 at.%, and N = 55.5 at.%. The contents of each element are all within the atomic percentage limits of the phase-shifting film 30 of this application (i.e., Mo atomic percentage ≤ 10 at.%, Si atomic percentage ≥ 30 at.%, and N atomic percentage ≥ 40 at.%).

[0096] The optical performance of the phase shift film 30 was simulated based on the above-mentioned measured parameters. The results show that the total transmittance of the phase shift film 30 and the etching stop film 20 is 6.0% and the total phase shift is 179.8° under 193nm wavelength light.

[0097] (4) Preparation of light-shielding film 40:

[0098] Three layers are sequentially deposited on the side of the phase-shifting film 30 away from the light-transmitting substrate 10 to obtain a light-shielding film 40 with a three-layer structure; wherein, the film layer close to the phase-shifting film 30 is the first light-shielding layer and the second light-shielding layer, and the film layer away from the phase-shifting film 30 is the third light-shielding layer.

[0099] The first light-shielding layer was deposited using DC reactive magnetron sputtering with a chromium (Cr) target. A mixture of Ar, N2, and O2 was used as the working gas (with a flow rate ratio of Ar, O2, and N2 of 24:5:30). The working gas pressure was set to 0.13 Pa, and the DC power supply was 450 W. A CrON film with a thickness of 18 nm was obtained. The chemical composition of the first light-shielding layer was determined by XPS (X-ray photoelectron spectroscopy), and the content of each element in the first light-shielding layer was found to be: Cr = 41 at.%, O = 49 at.%, N = 10 at.%.

[0100] The second light-shielding layer was also deposited using DC reactive magnetron sputtering with a chromium (Cr) target and a mixed gas of Ar, N2, and O2 as the working gas (with a gas flow ratio of Ar, O2, and N2 of 60:1:20). The working gas pressure was set to 0.13 Pa, and the DC power supply was 600 W. A CrON film with a thickness of 5 nm was obtained. The chemical composition of the second light-shielding layer was determined by XPS (X-ray photoelectron spectroscopy), and the content of each element in the second light-shielding layer was found to be: Cr = 55 at.%, O = 8 at.%, N = 37 at.%.

[0101] The third light-shielding layer was also deposited using DC reactive magnetron sputtering with a chromium (Cr) target and a mixture of Ar, N2, and O2 as the working gas (with a flow rate ratio of Ar, O2, and N2 of 24:5:30). The working gas pressure was set to 0.13 Pa, and the sputtering power was 450 W. A CrON film with a thickness of 21 nm was deposited. The chemical composition of the third light-shielding layer was determined by XPS (X-ray photoelectron spectroscopy), and the content of each element in the third light-shielding layer was found to be: Cr = 41 at.%, O = 49 at.%, N = 10 at.%.

[0102] The optical density OD of the etch stop film 20 / phase shift film 30 / light shielding film 40 stacked structure obtained in step (4) at a wavelength of 193 nm was measured using an ultraviolet spectrophotometer. The result was 3.2, which meets the requirement of optical density in the range of 2.9 to 3.3 of this application. The optical density of the light shielding film 40 was 1.98, which meets the requirement of optical density in the range of 1.5 to 2.1 of this application.

[0103] (5) Preparation of hard mask 50:

[0104] DC magnetron sputtering is performed on the side of the light-shielding film 40 away from the light-transmitting substrate 10. The target material is silicon (Si) target material, and a mixture of Ar and O2 gas is used as working gas (where the gas flow ratio of Ar and O2 is 1:5). The working gas pressure is set to 0.13 Pa, and the power of the DC power supply is 500 W, to obtain a SiO2 monolayer film (i.e., hard mask 50) with a thickness of 5 nm.

[0105] The chemical composition of the SiO2 monolayer film was determined by XPS (X-ray photoelectron spectroscopy), and the contents of each element in the SiO2 monolayer film were found to be: Si = 65.1 at.%, O = 34.9 at.%.

[0106] A schematic diagram of the cross-sectional structure of the mask blank obtained in Example 1 is shown below. Figure 1 As shown.

[0107] A method for manufacturing a phase-shifting mask, using the mask blank obtained in Example 1, includes:

[0108] (1) The surface of the hard mask 50 in the mask blank is treated with HMDS (hexamethyldisilazane) to improve the adhesion between the resist film 60 and the hard mask 50. A 100nm chemically amplified resist film 60 sensitive to electron beams is spin-coated on the surface of the hard mask 50. Then, it is exposed using an electron beam exposure machine with an exposure light source wavelength of 193nm. After baking and development, a first stacked structure containing a patterned first resist film 61 is obtained (e.g., Figure 3 (as shown);

[0109] (2) Using the patterned first resist film 61 in the first stacked structure as a mask, a mixed gas of SF6 and He with a gas flow ratio of 1:15 is used to dry etch the hard mask 50 in the first stacked structure. After removing the patterned first resist film 61 by wet cleaning, a second stacked structure containing the patterned hard mask 51 is obtained (e.g., ...). Figure 4 As shown), the cleaning agent is a combination of SPM (containing H2SO4, H2O2 and H2O), SCI (containing NH4OH, H2O2 and H2O) and deionized water;

[0110] (3) Using the patterned hard mask 51 as a mask, a mixed gas of Cl2 and O2 with a gas flow ratio of 10:1 is used to dry etch the light-shielding film 40 in the second stacked structure to obtain a third stacked structure containing the patterned first light-shielding film 41 (e.g., Figure 5 (as shown);

[0111] (4) Using the patterned first light-shielding film 41 in the third stacked structure as a mask, dry etching is performed on the phase shift film 30 in the third stacked structure using a mixed gas of SF6 and He with a gas flow ratio of 1:15. During the etching process in step (4), the patterned hard mask 51 is removed, resulting in a fourth stacked structure containing the patterned phase shift film 31 (e.g., ...). Figure 6 (as shown);

[0112] (5) A 150 nm thick chemically amplified resist film sensitive to electron beams is spin-coated onto the surface of the fourth stacked structure away from the light-transmitting substrate 10; then, it is exposed using an electron beam exposure machine with an exposure light source wavelength of 193 nm. After baking and development, a fifth stacked structure containing a patterned second resist film 62 is obtained (e.g., Figure 7 (as shown);

[0113] (6) Using the patterned second resist film 62 in the fifth stacked structure as a mask, the first light-shielding film 41 in the fifth stacked structure is dry etched with a mixed gas of Cl2 and O2 with a gas flow ratio of 7:2. During the etching process in step (6), the etching stop film 20 is completely consumed. After removing the patterned second resist film 62 by wet cleaning, a phase shift mask containing the patterned second light-shielding film 42 is obtained. Figure 8 A schematic diagram of the cross-sectional structure of the phase-shifting mask is shown.

[0114] Example 2

[0115] The difference from Example 1 is that the phase-shifting film 30 in the mask blank has a two-layer structure. Specifically, in the process of manufacturing the mask blank, step (3) of the preparation process of the phase-shifting film 30 includes:

[0116] A two-layer phase-shifting film 30 is obtained by direct current (DC) magnetron sputtering on the surface of the etching stop film 20 away from the transparent substrate 10. For the first layer, a molybdenum-silicon (MoSi) alloy target is used, and a mixture of Ar and N2 gas is used as the working gas (where N2 gas flow rate / (Ar gas flow rate + N2 gas flow rate) = 83.3%). The working gas pressure is set to 0.15 Pa, and the DC power supply is 500 W, resulting in a MoSiON monolayer film. The thickness of this first MoSiON monolayer film is 34 nm, and the content of each element is: Mo = 6.2 at.% and Si = 35.9 at.%. The elements were: Mo = 6.5 at.%, O = 11.2 at.%, and N = 46.7 at.%. For the second layer, a molybdenum-silicon (MoSi) alloy target was used, and a mixture of Ar and N2 was used as the working gas (where N2 gas flow rate / (Ar gas flow rate + N2 gas flow rate) = 80.0%). The working gas pressure was set to 0.14 Pa, and the sputtering power was 500 W, resulting in a MoSiON monolayer film. The thickness of this second MoSiON monolayer film was 38 nm, and the elemental contents were: Mo = 6.5 at.%, Si = 37.3 at.%, O = 9.5 at.%, and N = 46.7 at.%.

[0117] The preparation steps of the remaining mask blanks are the same as in Example 1; the optical density OD of the stacked structure of the etching stop film 20 / phase shift film 30 / light shielding film 40 obtained in step (4) was measured at a wavelength of 193nm using an ultraviolet spectrophotometer, and the result was 3.2; the optical performance of the phase shift film 30 was simulated based on the above-mentioned relevant measured parameters, and the results showed that the total transmittance of the phase shift film 30 and the etching stop film 20 was 6.2% and the total phase shift was 178.6° at a wavelength of 193nm;

[0118] The preparation steps of the phase-shifting mask are the same as in Example 1.

[0119] Example 3

[0120] The difference from Example 1 is that the light-shielding film 40 in the mask blank has a single-layer structure and its thickness is 45nm.

[0121] Deposition was performed using DC reactive magnetron sputtering with a chromium (Cr) target and a mixture of Ar, CO2, and N2 as the sputtering gas (with a flow rate ratio of Ar:CO2:N2 of 25:5:4). The working pressure was set to 0.3 Pa, and the DC power supply was 700 W. A CrONC film was obtained, with the following elemental contents: Cr = 40 at.%, O = 29 at.%, N = 17 at.%, C = 14 at.%.

[0122] The preparation steps of the remaining mask blanks are the same as in Example 1; the optical density OD of the stacked structure of the etching stop film 20 / phase shift film 30 / light shielding film 40 obtained in step (4) was measured at a wavelength of 193nm using an ultraviolet spectrophotometer, and the result was 3.1, of which the optical density of the light shielding film 40 was 1.91, which meets the requirement of the optical density of the light shielding film 40 in this application being in the range of 1.5 to 2.1;

[0123] The preparation steps of the phase-shifting mask are the same as in Example 1.

[0124] Comparative Example 1

[0125] The difference from Example 1 is that the preparation process of the mask blank in Comparative Example 1, specifically, the preparation process of the phase shift film 30 in step (3) is different from that in Example 1, including:

[0126] DC magnetron sputtering is performed on the side of the etching stop film 20 away from the light-transmitting substrate 10. The target material is a molybdenum-silicon (MoSi) alloy target. A mixture of Ar and N2 gas is used as the working gas (where N2 gas flow rate / (Ar gas flow rate + N2 gas flow rate) = 33%). The working gas pressure is set to 0.13 Pa, and the power of the DC power supply is 500 W, to obtain a MoSi monolayer film (i.e., phase-shifting film 30).

[0127] The chemical composition of the MoSi monolayer was determined by XPS (X-ray photoelectron spectroscopy), and the content of each element in the MoSi monolayer was found to be: Mo = 16.4 at.%, Si = 63.7 at.%, and N = 19.9 at.%. The above element contents are not within the atomic percentage limits of the phase-shifting film 30 of this application (Mo atomic percentage ≤ 10 at.%, Si atomic percentage ≥ 30 at.%, N atomic percentage ≥ 40 at.%).

[0128] The optical performance of the phase shift film 30 was simulated based on the aforementioned measured parameters. The results show that, at a light wavelength of 193 nm, within the allowable film thickness range (60–90 nm), neither the phase shift film 30 nor the etching stop film 20 fabricated on a transparent substrate can simultaneously meet the requirements for total transmittance and total phase difference of the phase shift film 30 and the etching stop film 20 (the transmittance of the etching stop film 20 and the phase shift film 30 under an exposure light source with a wavelength of 193 nm is 3–35%, and the phase difference is 175–182°).

[0129] Comparative Example 2

[0130] The difference from Example 1 is as follows: Figure 9As shown, the mask blank of Comparative Example 2 did not have an etching stop film 20. The thickness of the MoSi monolayer film (i.e., phase shift film 30) obtained in step (3) was 69 nm, and the contents of each element were: Mo = 4.9 at.%, Si = 39.9 at.%, and N = 55.2 at.%.

[0131] The elemental contents of the phase shift film 30 in the mask blanks prepared in Comparative Example 2 are all within the atomic percentage limits of the phase shift film 30 in this application (Mo atomic percentage ≤ 10 at.%, Si atomic percentage ≥ 30 at.%, N atomic percentage ≥ 40 at.%).

[0132] Based on the aforementioned measured parameters, the optical performance of the phase-shifting film 30 of the mask blank in Comparative Example 2 was simulated. The results show that the total transmittance of the etching stop film 20 and the phase-shifting film 30 under 193 nm wavelength light is 6.2%, and the total phase difference is 177.7°. The total transmittance and total phase difference of the etching stop film 20 and the phase-shifting film 30 are within the range of 3-35% transmittance and 175-182° phase difference of the etching stop film 20 and the phase-shifting film 30 under an exposure light source with a wavelength of 193 nm in this application. The optical density OD of the stacked structure of the phase-shifting film 30 and the light-shielding film 40 of the mask blank in Comparative Example 2 was measured using an ultraviolet spectrophotometer, and the result was 2.97, which meets the requirement of the optical density in the range of 2.9-3.3 in this application.

[0133] The process of preparing a binary mask using the mask blank obtained in Comparative Example 2 includes the following steps:

[0134] (1) The surface of the hard mask 50 in the mask blank is treated with HMDS (hexamethyldisilazane) to improve the adhesion between the resist film 60 and the hard mask 50. A chemically amplified resist film 60 with a thickness of 100 nm and sensitive to electron beam is spin-coated on the surface of the hard mask 50. Then, it is exposed using an electron beam exposure machine with an exposure light source wavelength of 193 nm. After baking and development, a first stacked structure containing a patterned first resist film 61 is obtained (e.g., Figure 3 (as shown);

[0135] (2) Using the patterned first resist film 61 in the first stacked structure as a mask, a mixed gas of SF6 and He with a gas flow ratio of 1:15 is used to dry etch the hard mask 50 in the first stacked structure. After removing the patterned first resist film 61 by wet cleaning, a second stacked structure containing the patterned hard mask 51 is obtained (e.g., ...). Figure 4 (as shown);

[0136] (3) Using the patterned hard mask 51 as a mask, a mixed gas of Cl2 and O2 with a gas flow ratio of 10:1 is used to dry etch the light-shielding film 40 in the second stacked structure to obtain a third stacked structure containing the patterned first light-shielding film 41 (e.g., Figure 5 (as shown);

[0137] (4) Using the patterned first light-shielding film 41 in the third stacked structure as a mask, dry etching is performed on the phase shift film 30 in the third stacked structure using a mixed gas of SF6 and He with a gas flow ratio of 1:15. During the etching process in step (4), the patterned hard mask 51 is removed, resulting in a fourth stacked structure containing the patterned phase shift film 31 (e.g., ...). Figure 6 (as shown);

[0138] (5) A 150 nm thick, electron beam-sensitive chemically amplified resist film is spin-coated onto the side of the fourth stacked structure away from the transparent substrate 10; then, it is exposed using an electron beam exposure machine with an exposure light source wavelength of 193 nm. After baking and development, a fifth stacked structure containing a patterned second resist film 62 is obtained (e.g., Figure 7 (as shown);

[0139] (6) Using the patterned second resist film 62 in the fifth stacked structure as a mask, the first light-shielding film 41 in the fifth stacked structure is dry etched with a mixed gas of Cl2 and O2 with a gas flow ratio of 7:2. After removing the patterned second resist film 62 by wet cleaning, a phase shift mask containing the patterned second light-shielding film 42 is obtained.

[0140] Upon observation, the transparent substrate 10 of the phase-shifting mask in Comparative Example 2 was over-etched, and the over-etching exhibited unevenness, which led to uneven phase shifting during the subsequent pattern transfer process.

[0141] As can be seen from the above description, the embodiments of the present invention achieve the following technical effects:

[0142] The mask blank provided in this application is provided with an etching stop film 20. Compared with a mask blank without an etching stop film 20, during the etching of the phase shift film 30, over-etching of the light-transmitting substrate 10 can be avoided, thus improving the uniformity of optical performance during the subsequent pattern transfer process. Compared with other types, the etching stop film 20 using the aforementioned specific material, and the material of the etching stop film 20 being different from that of the phase shift film 30 and the light-transmitting substrate 10, is beneficial in preventing over-etching of the light-transmitting substrate 10 and improving the uniformity of optical performance during the subsequent pattern transfer process.

[0143] Compared to other types, the phase-shifting film 30 made of the aforementioned specific material can optimize the light field distribution, enable destructive interference, reduce the brightness of dark areas in the light field, and increase the brightness of bright areas, thereby improving the resolution of the fabricated phase-shifting mask and reducing the linewidth. Furthermore, compared to other ranges, limiting the optical density of the etching stop film 20, the phase-shifting film 30, and the light-shielding film 40 to the aforementioned specific range allows the mask blank to effectively block the exposure light source, improving the resolution of the phase-shifting mask and consequently increasing the resolution of the pattern formed on the wafer surface.

[0144] It should be noted that the terms "first," "second," etc., used in the specification and claims of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such terms can be used interchangeably where appropriate so that the embodiments of this application described herein can be implemented, for example, in a sequence other than those described herein.

[0145] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A mask blank, characterized in that, The mask blank comprises a light-transmitting substrate (10), an etching stop film (20), a phase-shifting film (30), a light-shielding film (40), and a hard mask (50) stacked sequentially, wherein, The material of the etching stop film (20) includes metallic and non-metallic elements, wherein the metallic elements are selected from one of Cr, Ta, Hf, Zr, Al, W and Ni; The phase-shifting film (30) is made of molybdenum-silicon compounds and non-metallic elements; The material of the light-shielding film (40) includes Cr and non-metallic elements; The material of the hard mask (50) includes silicon or molybdenum silicon compounds and non-metallic elements; The nonmetallic element is selected from one or more of C, O, N, B and P; The optical density of the light-shielding film (40) under the exposure light source of ArF excimer laser is 1.5 to 2.1; The optical density of the stacked structure obtained by sequentially stacking the etching stop film (20), the phase shift film (30) and the light-shielding film (40) under the exposure source of ArF excimer laser is 2.9 to 3.

3. The transmittance of the etching stop film (20) and the phase shift film (30) under an exposure light source with a wavelength of 193 nm is 3-35%, and the phase difference is 175-182°.

2. The mask blank according to claim 1, characterized in that, The etching stop film (20) is a single-layer or multi-layer structure with a thickness of 1 to 10 nm. In each layer of the etching stop film (20), the atomic percentage of Cr is ≥30 at.%, the atomic percentage of C is ≤15 at.%, and the remainder is other elements.

3. The mask blank according to claim 1, characterized in that, The phase-shifting film (30) has a single-layer or multi-layer structure with a thickness of 60–90 nm.

4. The mask blank according to claim 3, characterized in that, The phase-shifting film (30) is a single-layer structure, wherein the atomic percentage of Mo is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤20 at.%, and the atomic percentage of N is ≥40 at.%.

5. The mask blank according to claim 3, characterized in that, The phase-shifting film (30) has a two-layer structure. The atomic percentage of O in the film layer on the side away from the etching stop film (20) is lower than that in the film layer on the side closer to the etching stop film (20). Specifically, the atomic percentage of Mo in the film layer on the side closer to the etching stop film (20) is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤25 at.%, and the atomic percentage of N is ≥35 at.%; the atomic percentage of Mo in the film layer on the side away from the light-transmitting substrate (10) is ≤10 at.%, the atomic percentage of Si is ≥30 at.%, the atomic percentage of O is ≤20 at.%, and the atomic percentage of N is ≥40 at.%; the thickness of the film layer on the side closer to the etching stop film (20) is 5–45 nm, and the thickness of the film layer on the side away from the etching stop film (20) is 30–70 nm.

6. The mask blank according to claim 1, characterized in that, The light-shielding film (40) has a single-layer or multi-layer structure with a thickness of 30–65 nm.

7. The mask blank according to claim 6, characterized in that, The light-shielding film (40) has a single-layer structure, wherein the atomic percentage of Cr is ≥30 at.%, the sum of the atomic percentages of O and N is ≤55 at.%, and the atomic percentage of C is ≤15 at.%.

8. The mask blank according to claim 6, characterized in that, The light-shielding film (40) has a two-layer structure. The relative refractive index of the film layer on the side away from the phase-shifting film (30) is greater than that on the side closer to the phase-shifting film (30). In the film layer on the side closer to the phase-shifting film (30), the atomic percentage of Cr is ≤43 at.%, the sum of the atomic percentages of O and N is ≥37 at.%, and the atomic percentage of C is ≤20 at.%. In the layer on the side away from the phase-shifting film (30), the atomic percentage of Cr is ≥35 at.%, and the sum of the atomic percentages of O and N is ≤65 at.%. The thickness of the film layer on the side closer to the phase-shifting film (30) is 35-55 nm, and the thickness of the layer on the side away from the phase-shifting film (30) is 2-10 nm.

9. The mask blank according to claim 8, characterized in that, The light-shielding film (40) further includes a diffusion-blocking layer, which is disposed on the side close to the phase-shifting film (30), wherein the atomic percentage of Cr in the diffusion-blocking layer is ≥35 at.%, and the sum of the atomic percentages of O and N is ≤65 at.%; the thickness of the diffusion-blocking layer is 2 to 10 nm.

10. The mask blank according to claim 6, characterized in that, The light-shielding film (40) has a three-layer structure, comprising a first light-shielding layer, a second light-shielding layer, and a third light-shielding layer stacked in sequence. The first light-shielding layer is disposed on the side close to the phase-shifting film (30), and the third light-shielding layer is disposed on the side away from the phase-shifting film (30). In the first light-shielding layer, the atomic percentage of Cr is ≤45 at.%, the sum of the atomic percentages of O and N is ≥35 at.%, and the atomic percentage of C is ≤20 at.%. In the second light-shielding layer, the atomic percentage of Cr is ≥45 at.%, and the atomic percentage of non-metallic elements is ≤55 at.%. In the third light-shielding layer, the atomic percentage of Cr is ≤45 at.%, the sum of the atomic percentages of O and N is ≥35 at.%, and the atomic percentage of C is ≤20 at.%. The thickness of the first light-shielding layer is 10–35 nm, the thickness of the second light-shielding layer is 2–10 nm, and the thickness of the third light-shielding layer is 10–30 nm.

11. The mask blank according to claim 6, characterized in that, The light-shielding film (40) has a four-layer structure, comprising a first light-shielding layer, a second light-shielding layer, a third light-shielding layer, and a fourth light-shielding layer stacked in sequence. The first light-shielding layer is disposed on the side close to the phase-shifting film (30), and the fourth light-shielding layer is disposed on the side away from the phase-shifting film (30). Specifically, in the first light-shielding layer, the atomic percentage of Cr is ≤45 at.%, the sum of the atomic percentages of O and N is ≥40 at.%, and the atomic percentage of C is ≤15 at.%; in the second light-shielding layer, the atomic percentage of Cr is ≥35 at.%, and the atomic percentage of the third non-metallic element is ≤65 at.%; in the third light-shielding layer, the atomic percentage of Cr is ≤45 at.%, the sum of the atomic percentages of O and N is ≥40 at.%, and the atomic percentage of C is ≤15 at.%; in the fourth light-shielding layer, the atomic percentage of Cr is ≥35 at.%, and the sum of the atomic percentages of O and N is ≤65 at.%; the thickness of the first light-shielding layer is 15–30 mm. The thickness of the second light-shielding layer is 2-10 nm, the thickness of the third light-shielding layer is 15-30 nm, and the thickness of the fourth light-shielding layer is 2-10 nm.

12. The mask blank according to claim 1, characterized in that, The hard mask (50) is a single-layer or multi-layer structure with a thickness of 2 to 15 nm. In each layer of the hard mask (50), the atomic percentage of Si is ≥30 at.%, and the sum of the atomic percentages of O and N is ≤70 at.%.

13. The mask blank according to claim 1, characterized in that, The mask blank also includes a resist film (60), which is disposed on the surface of the hard mask (50) away from the light-transmitting substrate (10); the thickness of the resist film (60) is 60 to 200 nm.

14. A method for manufacturing a mask blank according to any one of claims 1 to 13, characterized in that, An etching stop film (20), a phase shift film (30), a light-shielding film (40), and a hard mask (50) are sequentially deposited on one side surface of a light-transmitting substrate (10).

15. The method for manufacturing a mask blank according to claim 14, characterized in that, The deposition is performed using magnetron sputtering. During the deposition of the etching stop film (20), the phase shift film (30), the light-shielding film (40), and the hard mask (50), the working pressure is independently 0.1 to 0.4 Pa, the sputtering power is independently 200 to 3500 W, and the working gas is independently one or more of Ar, He, O2, N2, N2O, NO, NO2, CO2, CO, and CH4.

16. A method for manufacturing a phase-shifting mask, characterized in that, The phase-shifting mask is manufactured using the mask blank as described in claim 1 as raw material, and the manufacturing method includes: Step S1: A first resist is coated on the side of the hard mask (50) away from the light-transmitting substrate (10) in the mask blank to form a resist film (60). Exposure, baking and development are performed in sequence to obtain a first stacked structure containing a patterned first resist film (61). The exposure light source is an ArF excimer laser. Step S2: Using the patterned first resist film (61) in the first stacked structure as a mask, the hard mask (50) in the first stacked structure is etched, and after cleaning to remove the patterned first resist film (61), a second stacked structure containing the patterned hard mask (51) is obtained. Step S3: Using the patterned hard mask (51) in the second stacked structure as a mask, the light-shielding film (40) in the second stacked structure is etched to obtain a third stacked structure containing the patterned first light-shielding film (41). Step S4: Using the patterned first light-shielding film (41) in the third stacked structure as a mask, the phase shift film (30) in the third stacked structure is etched. During the etching process in step S4, the patterned hard mask (51) is removed, and a fourth stacked structure containing the patterned phase shift film (31) is obtained. Step S5: A second photoresist is coated on the side of the fourth stacked structure away from the light-transmitting substrate (10), and exposure, baking and development are performed sequentially to obtain a fifth stacked structure containing a patterned second photoresist film (62); the exposure light source is an ArF excimer laser. In step S6, the patterned second resist film (62) in the fifth stacked structure is used as a mask to etch the first light-shielding film (41) in the fifth stacked structure. During the etching process in step S6, the etching stop film (20) is etched away. After cleaning and removing the patterned second resist film (62), the phase shift mask containing the patterned second light-shielding film (42) is obtained.

17. The method for manufacturing a phase-shifting mask according to claim 16, characterized in that, The hard mask (50) is a single-layer structure, or the hard mask (50) is a two-layer structure, including a first hard mask layer and a second hard mask layer stacked in sequence. The first hard mask layer is disposed between the light-shielding film (40) and the second hard mask layer, wherein the etching rate of the first hard mask layer is lower than the etching rate of the second hard mask layer. Alternatively, the hard mask (50) has a three-layer structure, including a third hard mask layer, a fourth hard mask layer and a fifth hard mask layer stacked sequentially. The third hard mask layer is disposed between the light-shielding film (40) and the fourth hard mask layer, wherein the etching rate of the fourth hard mask layer is lower than the etching rate of the third hard mask layer and the etching rate of the fifth hard mask layer, respectively.

18. A phase-shifting mask, characterized in that, The phase-shifting mask is manufactured using the manufacturing method of the phase-shifting mask as described in claim 16 or 17.

Citation Information

Patent Citations

  • Mask blank, phase shift mask, method for manufacturing phase shift mask, and method for manufacturing semiconductor device

    CN115769144A

  • Phase shift mask blank, process for preparation of phase shift mask blank, phase shift photomask and manufacturing method thereof

    TW200528915A